Frequency of ventricular arrhythmias in apparently healthy, large breed dogs during seven-day Holter monitoring - Tamilselvam Gunasekaran; Alyssa Pinkos; Robert Sanders (PLoS ONE, 2025)
Continuous ambulatory electrocardiographic monitoring (Holter) is commonly used to diagnose and manage various cardiac arrhythmias in dogs. Despite its widespread use, data on the frequency of ventricular arrhythmias and its day-to-day variability in healthy, large-breed dogs without known predisposition to cardiomyopathy remains limited. This study assessed the frequency, complexity, and spontaneous day-to-day variation of ventricular arrhythmias in clinically healthy, large-breed dogs using seven-day Holter monitoring. Thirty-one, apparently healthy dogs without any history of systemic illness and normal physical examination findings underwent continuous 7-day Holter monitoring. Two dogs were excluded due to the occurrence of significant systemic disease soon after enrolment. The results from 29 dogs showed that most dogs (86%) had fewer than twenty ventricular premature complexes (VPCs) per 24-hour period, with significant day-to-day variation (up to 93%) in 4 dogs with over twenty VPCs. Complex ventricular arrhythmias, such as ventricular couplets, triplets, and ventricular tachycardia, were rare. No correlation was found between age and VPC frequency (p = 0.409) in this population of predominantly older dogs. These findings suggest that large-breed dogs without a predisposition to cardiomyopathies exhibit low arrhythmia frequencies with significant day-to-day variation in some dogs.